IMPROVING STUDENT LEARNING OUTCOMES IN INDONESIAN LANGUAGE USING THE COOPERATIVE SCRIPT METHOD IN CLASS VIII-1 SMP NEGERI 2 MUARA T.A 2018/2019 - Togatorof, Marlene (Universitas Dharmawangsa, 2020)
The problems in this research are: 1) Teachers do not use varied methods, but still tend to use lecture and question and answer methods, so that student learning outcomes in Indonesian lessons are still low 2) Teachers do not use media or props in Indonesian language learning, so students are not active in the teaching and learning process 3) Students feel bored with Indonesian lessons. The purpose of this research is to improve student learning outcomes in Indonesian language lessons on News Writing material using the Cooperative Script method in Class VIII-1 of SMP Negeri 2 Muara in the 2014/2015 academic year. The formulation of the problem in this research is Can it improve student learning outcomes in Indonesian language lessons on News Writing material using the Cooperative Script method for Class VIII-1 SMP Negeri 2 Muara in the 2018/2019 academic year? This type of research is classroom action research. In this study, the Cooperative Script Method is the main target. Applying the Cooperative Script Method in Indonesian language lessons on News Writing material can improve student learning outcomes in Class VIII-1 of SMP Negeri 2 Muara in the 2018/2019 academic year. The subjects of this study were 34 students of Class VIII-1, 11 boys and 23 girls. Formal objects using the Cooperative Script method in Indonesian language lessons at SMP Negeri 2 Muara for the 2018/2019 academic year. The results of the research at the time of the pre-test 5 students or 14.7% were complete and 29 students or 85.3% did not reach the completeness value of 34 students with a class average score of 47.64, the lowest score was 20 and the highest score is 80. In cycle I, the number of students who completed 19 students or 55.8% and 15 students who did not complete or equal to 44.2% with a class average score of 62.64, the lowest score was 40 and the highest score was 90. Meanwhile, in the second cycle the number of students who completed an increase was 31 students or 91.2% and 3 students who did not achieve the completeness score or 8.8% with an average score of 83.82, the lowest score was 50 and the highest score was 100. With Thus, it can be concluded that applying the Cooperative Script method can improve student learning outcomes in Indonesian language lessons on News Writing material in Class VIII-1 SMP Negeri 2 Muara for the 2018/2019 academic year